2005
DOI: 10.1103/physreve.71.036624
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized vortices in layered Kerr media

Abstract: In this letter we demonstrate the possibility of stabilizing beams with angular momentum propagating in Kerr media. Large propagation distances without filamentation can be achieved in layered media with alternating focusing and defocusing nonlinearities. Stronger stabilization can be obtained with the addition of an incoherent beam.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…For the vortex solitons with S ≥ 1, the numerical analysis reveals an internal stability boundary, β stability (S) < β collapse (S), the vortices being stable at β < β stability (S), see Table 1. In the interval of β stability (S) < β < β collapse (S), they are broken by azimuthal perturbations into rotating necklace-shaped clusters of fragments, which resembles the initial stage of the instability development of localized vortices in usual models; however, unlike those models [244][245][246] The stability boundary, β stability (S), can be found in an approximate analytical form too [85]. To this end, the wave function of an azimuthally perturbed vortex ring is approximated by…”
Section: B Basic Results For Vortex Solitonsmentioning
confidence: 99%
“…For the vortex solitons with S ≥ 1, the numerical analysis reveals an internal stability boundary, β stability (S) < β collapse (S), the vortices being stable at β < β stability (S), see Table 1. In the interval of β stability (S) < β < β collapse (S), they are broken by azimuthal perturbations into rotating necklace-shaped clusters of fragments, which resembles the initial stage of the instability development of localized vortices in usual models; however, unlike those models [244][245][246] The stability boundary, β stability (S), can be found in an approximate analytical form too [85]. To this end, the wave function of an azimuthally perturbed vortex ring is approximated by…”
Section: B Basic Results For Vortex Solitonsmentioning
confidence: 99%
“…These include the use of competing (cubicquintic [13]- [15] or quadratic-cubic [16]) nonlinearities, trapping configurations [17], and, as demonstrated experimentally [18] and theoretically [19], periodic lattice potentials. The stabilization may be enhanced by "management" techniques, i.e., periodic alternation of the sign of the nonlinear term [20]. Another possibility for the stabilization is provided by the use of nonlocal nonlinearity [21].…”
mentioning
confidence: 99%
“…On the other hand, in a recent work [129] it was demonstrated that a two-component (vectorial) generalization of the present model may support stable existence, in the course of very long time, of compound solitons in which one component is arranged as a (partly incoherent) fundamental soliton, while the other one carries vorticity.…”
Section: Direct Numerical Resultsmentioning
confidence: 48%